Validating the classics: Accurate reference gene panel for reliable RT-qPCR in Porifera - Kseniia V. Skorentseva; Nikolai P. Melnikov; Alexander V. Ereskovsky; Andrey I. Lavrov; Aleena A. Saidova (PLoS ONE, 2026)
Quantitative real-time PCR (RT-qPCR) is a powerful method for gene expression analysis, but its accuracy critically depends on the selection of stable reference genes for normalization. In non-model organisms such as sponges (phylum Porifera), this task is complicated with high biological variability, seasonal fluctuations, and limited molecular resources. In this study, we first identified and validated candidate reference genes in the calcareous sponge Leucosolenia corallorrhiza . Seven commonly used housekeeping genes ( ACT1, GAPDH, RPL13A, HPRT1, RPS3A, TBP, LMN1 ) were selected based on available transcriptomic and genomic data, and their expression stability was evaluated using geNorm, NormFinder, BestKeeper, and RefFinder under physiological conditions and during tissue regeneration. RPL13A, ACT1 , and GAPDH were identified as the most stable reference genes in L. corallorrhiza . To assess whether reference genes identified in L. corallorrhiza can be applied more broadly, we extended the analysis to three phylogenetically and ecologically distinct sponge species: Halisarca dujardinii (marine demosponge), Ephydatia fluviatilis (freshwater demosponge), and Lycopodina hypogea (carnivorous marine demosponge). The same panel of candidate genes was evaluated in all species using the same analytical approaches. Although similar subsets of genes (including RPL13A, ACT1, and GAPDH ) consistently ranked among the most stable candidates, no single gene exhibited universal stability across all species. Pairwise variation analysis indicated that the use of two reference genes is sufficient for accurate normalization, while the geometric mean of three top-ranked genes further improves reproducibility and reduces the risk of false-positive results, as demonstrated performing RHOA normalization. Overall, our results demonstrate that reference gene stability in sponges is species-specific and cannot be reliably predicted based on ecological or phylogenetic grouping alone. At the same time, we define a robust panel of candidate reference genes that can serve as a starting point for RT-qPCR studies in Porifera, provided that species- and condition-specific validation is performed. Our study also highlights that technical challenges inherent to research on non-model organisms must be carefully considered in the design of future studies.